An IoT-Based Autonomous Waiter Robot - Sadiq Ur Rehman (Memoria Investigaciones en Ingeniería)
The widespread adoption of automation and robotics across various sectors has driven innovations in service delivery, particularly in the hospitality industry. This paper presents the design, development, and implementation of an IoT-based waiter robot aimed at enhancing efficiency and customer satisfaction in restaurants. The robot employs an ESP32 microcontroller, ultrasonic sensors, and a touchscreen interface for autonomous navigation, order processing, and food delivery. Unlike traditional path-planning approaches, this robot adapts dynamically to its environment, offering flexibility and reliability in service. Detailed evaluations demonstrate the system’s effectiveness in optimizing operations, reducing delays, and improving overall customer experience. The proposed solution is cost-effective and scalable, making it suitable for diverse restaurant settings.